Karakteristik Pemikiran Hukum Perkawinan Imam Al-Ghazali dalam Ihya’ Ulum Al-Din - Salam, Nor (HOKI : Journal of Islamic Family Law, 2024)
This research focuses on al-Ghazali's thoughts regarding marriage law as outlined in his masterpiece, Ihya' Ulum al-Din. To track the focus of the research, a descriptive-analytical research method was used. Through this method, a finding was produced regarding the characteristics of al-Ghazali's thinking regarding marriage law, namely the inadequate explanation of the hadith he quoted, both in terms of istinbath al-ahkam and its validity status. This also includes quoting misogynist hadiths. This was caused by al-Ghazali's obsession with composing Ihya' which was not intended to explain the propositions but rather to provide guidance for every Muslim to obtain Allah's approval.